Multicultural and Multilingual Inside Education Perspective - Sudirman, A.M. Oleh; Dacholfany, dan M. Ihsan (International Journal of Criminology and Sociology, 2022)
The purpose of the description of this study is to create a just and democratic safe society; security, justice and democracy can be achieved by diagnosing conflict as sublimation for differences in the language and culture of society. So that multicultural, multilingual education at least minimizes local, national and global community noise in overcoming vertical-horizontal conflicts. This study uses methods and techniques for analyzing general domain cultural themes to cultural sub themes; linear system relationships between components in education. The concept of multicultural, multilingual conflicting heterogeneity communities can help multicultural learning with the cultural-lingual approach; multimedia, multimetodic, multisite against the conflict of the heterogeneity community typically in the islands of the coast. Conflicting heterogeneity society is used as multicultural media learning media diagnostic material. Contrastive analysis of language and cultural conflicts is very helpful in diagnosing sublimation in an educational perspective. Hopefully the concepts of multicultural and multilingual community conflict in heterogeneity contribute in an educational perspective, namely multicultural and multilingual synthesis of local, national, and global in society elements.